Determinan terhadap Timbulnya Skizofrenia pada Pasien Rawat Jalan di Rumah Sakit Jiwa Prof. Hb Saanin Padang Sumatera Barat - Erlina Soewadi, Dibyo Pramono (Berita Kedokteran Masyarakat (BKM), 2010)
Background: According to the survey on mental disorder as many as 44.6 per 1000 Indonesian population in 1995 had serious mental disorder such as schizophrenia. This shows significant increase if compared  to data of 1980 whereby only 1 – 2 per 1000 Indonesian population were schizophrenic. In Prof. HB. Saanin Mental Hospital Padang 2007 the number of outpatient visits at organic mental disorder polyclinic were as many as 10,812 people with 5397 people (49.9) were schizophrenic patients.Objectives: To identify factors affecting the prevalence of schizophrenia among outpatients at Prof. HB. Saanin Mental Hospital Padang Sumatera Barat.Methods: This was a case control study with patients of 17.35 years old visiting organic mental disorder polyclinic of Prof. HB. Saanin Mental Hospital Padang as population. Samples were taken using non probability sampling with fixed disease sampling technique. Data analysis used bivariable method with simple logistic statistical test; multivariable method with logistic regression statistical test to measure the relationship between psychosocial, socio cultural and socio demographic factors and the prevalence of schizophrenia. Relationship among variables was measured using OR with CI 95% and p=0.05.Results: Factors related to the incidence of schizophrenia at organic mental disorder polyclinic of Prof. HB. Saanin Mental Hospital Padang based on bivariable analysis were sex (OR=2.37 (95%CI; 1.14 – 4.96), occupation OR=4.33 (95%CI; 1.85-10.29), failure to achieve ideals OR=2.82 (95%CI; 1.38 – 5.78), family rearing  pattern OR=1.71 (95%CI; 0.85 – 3.44), economic status OR=6.000 (95%CI; 2.52 – 14.60), on multivariabel analysis the most dominant factor affecting the incidence of schizophrenia were economic status OR=7,482 (95%CI; 2.852 – 19.657), p=0.000.Conclusions: There was significant effect of sex, occupational and social economic factors to the incidence of schizophrenia and non schizophrenia. Family rearing pattern was not the greatest factor that affected the prevalence of schizophrenia.Keywords:  schizophrenia, psychological factors, socio cultural factors, socio demographic factors